Unseen crisis: Revealing the hidden health impact of indoor air pollution—A scoping review - Ranjana G. Chavan; Jasneet Kaur; Gopal S. Charan (Journal of Education and Health Promotion)
Indoor air pollution presents a critical public health challenge, particularly in countries such as India, where millions are exposed to harmful pollutants within their homes and workplaces. This scoping review delves into the multifaceted impacts of indoor air pollution on health outcomes, synthesizing evidence from various study designs and geographical regions A scoping review was conducted. Drawing on a comprehensive search strategy, which yielded 320 records, wherein 120 in PubMed, 108 in Web of Science, and 92 in SCOPUS. Ten studies were selected based on predefined inclusion criteria, totaling a sample size of 37,43166 individuals. The synthesis of findings from the selected studies reveals the multifaceted impact of indoor air pollution on health status. Respiratory symptoms and illnesses were found to be prevalent among individuals exposed to indoor pollutants, with biomass fuel combustion posing a particularly high risk for chronic obstructive pulmonary disease (COPD) in women. In addition, indoor air pollution was associated with adverse pregnancy outcomes, cardiovascular diseases, central nervous system impacts, cognitive impairment, and developmental delays. Urgent action is needed to reduce indoor air pollution, safeguard health, and promote cleaner technologies for healthier indoor environments. Vulnerable populations, such as women, children, and the elderly, are disproportionately affected by indoor pollutants, highlighting the importance of targeted interventions and policies.